THE The Role of Exercise Physiology in Improving Physical Fitness: A Systematic Literature Review - Habil Tuqya; Wawan Junresti Daya; Tri Bayu Norito; Boy Indrayana; Ilham (S&Co Publishing, 2026)
Abstracts: Physical fitness is an important indicator of health and physical performance that enables individuals to perform daily activities efficiently without excessive fatigue. Exercise physiology provides scientific knowledge regarding the body's responses and adaptations to physical activity and training programs. This study aimed to examine the role of exercise physiology in improving physical fitness through a Systematic Literature Review (SLR). Literature was collected from Google Scholar using the Publish or Perish application with the keywords